A new functional IDH2 genetic variant is associated with the risk of lung cancer. Issue 3 (24th October 2016) - Li, Jiangjiang; Lu, Jingchen; He, Ya; Wu, Yong; Wu, Yuan; Song, Xin; Jiang, Yuee; Tang, Min; Weng, Xinxian; Yi, Wei; Luo, Xiangjian; Sun, Lunquan; et al.
Abstract : Recently, mutations in isocitrate dehydrogenase 1/2 (IDH1/2) were discovered in 70% of low‐grade glioma and secondary glioblastoma multiforme. The discovery of an oncogenic function and the identification of onco‐metabolites of IDH1/2 support new roles for metabolism in cancer. For example, some evidence indicates that IDH2 might also exhibit oncogenic functions by promoting cellular metabolism and cancer cell growth. We examined the association between IDH2 rs11540478 and lung cancer risk in 262 lung cancer patient cases and 602 healthy control subjects and also investigated the biological function of rs11540478 in vivo. We found that a higher risk was observed in lung cancer patient carriers of rs11540478 TT and CT compared with CC carriers (OR = 1.44; 95%CI = 1.04–2.00; P  = 0.03). The frequency of IDH2 rs11540478 TT and CT carriers was decreased in healthy individuals between the ages of 50–77 compared to those aged 30–49 (OR = 0.67; 95%CI = 0.47–0.96; P  = 0.03). Functional analysis showed the effect of rs11540478 on IDH2 expression and lung cancer cell viability, with higher IDH2 expression and cell viability among T allele compared with C allele. IDH2 mRNA was higher in peripheral blood lymphocytes from lung cancer patients compared to healthy subjects. Herein, for the first time we identified IDH2 rs11540478 as a new susceptibility locus for lung cancer. The effect of rs11540478 on mRNA expression of IDH2 and lung cancer cell viability might provide new insight for the genetic basis of lung cancer. © 2016 Wiley Periodicals, Inc.